A intenção de cursar o ensino superior a partir da teoria da ação planejada - Sobral, Helenizia Santos (2019)
Many factors may influence the decision-making of high school graduates regarding college entrance. This research had the objective of analyzing the intention to attend higher education, by the students of high school, based on the Theory of Planned Action (TAP) that is organized based on the beliefs that influence human action. The study was divided into three chapters corresponding to the articles formulated for presentation. The objective of the first article was to carry out a systematic review on Brazilian psychology studies about professional orientation. It has been found that there are more empirical studies involving the subject, and that in the last years the publications have diminished considerably compared to the past decade. The second article sought to identify the beliefs about the intention to attend higher education based on TAP. In this study of qualitative and exploratory approach, semi-structured interviews were conducted with 20 high school students from the state public network of Alagoas. With this, we verified that the behavioral intention received a greater influence of the control beliefs. That is, the perception of knowing how to deal with the facilities and difficulties in attending higher education became preponderant in relation to social pressure and the analysis of the importance attributed to the behavior itself. The third article, which compose the quantitative stage of the research, had as objective to analyze the beliefs about the intention to attend higher education from the TAP, based on the identification of these beliefs and in the elaboration and validation of an instrument capable of evaluating them. The results showed that the Higher Education Intention Scale (ICES) is conceptually appropriate, consistent with the factors it measures and is accessible to the students who participated in the research. For the evaluated sample the attitude and the perception of behavioral control were the prevalent variables in the intention to attend higher education. The subjective norm showed an opposite influence in intention, that is, the lower the social pressure, the greater the interest in attending higher education. This finding may be related to the students' need to exercise autonomy when making their choices.